A single-cell landscape of triptolide-associated testicular toxicity in mice - Wei Zhang; Siyu Xia; Jinhuan Ou; Min Cao; Guangqing Cheng; Zhijie Li; Jigang Wang; Chuanbin Yang (Elsevier, 2023)
Triptolide is a key active component of the widely used traditional Chinese herb medicine Tripterygium wilfordii Hook. F. Although triptolide exerts multiple biological activities and shows promising efficacy in treating inflammatory-related diseases, its well-known safety issues, especially reproductive toxicity has aroused concerns. However, a comprehensive dissection of triptolide-associated testicular toxicity at single cell resolution is still lacking. Here, we observed testicular toxicity after 14 days of triptolide exposure, and then constructed a single-cell transcriptome map of 59,127 cells in mouse testes upon triptolide-treatment. We identified triptolide-associated shared and cell-type specific differentially expressed genes, enriched pathways, and ligand-receptor pairs in different cell types of mouse testes. In addition to the loss of germ cells, our results revealed increased macrophages and the inflammatory response in triptolide-treated mouse testes, suggesting a critical role of inflammation in triptolide-induced testicular injury. We also found increased reactive oxygen species (ROS) signaling and downregulated pathways associated with spermatid development in somatic cells, especially Leydig and Sertoli cells, in triptolide-treated mice, indicating that dysregulation of these signaling pathways may contribute to triptolide-induced testicular toxicity. Overall, our high-resolution single-cell landscape offers comprehensive information regarding triptolide-associated gene expression profiles in major cell types of mouse testes at single cell resolution, providing an invaluable resource for understanding the underlying mechanism of triptolide-associated testicular injury and additional discoveries of therapeutic targets of triptolide-induced male reproductive toxicity.